Alan Irwin, Citizen Science - Hannah Mowat (Opticon1826, 2011)
As one follows the climate negotiations, year after year, one cannot help but feel frustrated, and wonder how we got to this impasse between policy-makers – who are advocating techno-fixes to engineer our way out of the problem, and citizens – who are pushing for democratic, sustainable, people-oriented solutions. To illustrate this, I present two dichotomous initiatives to the climate change crisis: on one hand, the Cochabamba People’s agreement, calling for a ‘global referendum or popular consultation on climate change in which all are consulted’ and the Copenhagen Accord on the other where a handful of world leaders – technocrats – tried to take the planet’s future into their own hands.